2020
DOI: 10.24926/iip.v11i1.2434
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pharmacy Characteristics and Customer Quality of Life on Satisfaction of Community Pharmacy Customers

Abstract: Objectives: The study objectives were to evaluate customer satisfaction with community pharmacy services and measure the relationships between customer satisfaction and pharmacy/pharmacist characteristics and customer quality of life. Methods: This was a cross-sectional survey of a convenience sample of customers at 20 community pharmacies in 10 different geographical areas in Baghdad city between May and September 2018. We used the satisfaction items which were developed by Paterson and colleagues in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… 45 46 49 52 59 83 113 Of the remaining studies, four each were from Japan, 57 61 62 79 the Netherlands 55 102–104 and Thailand 67 69 95 105 ; three each from Germany, 58 75 108 Estonia, 71 78 115 Iran 48 76 84 and Vietnam 93 96 97 and two each were from Lebanon, 112 114 UAE, 60 86 Brazil 107 110 and Spain. 63 73 One each from Canada, 74 Finland, 99 New Zealand, 43 Lithuania, 44 Malaysia, 87 Poland, 91 Slovenia, 80 Serbia, 70 Sudan, 94 Nigeria, 109 Iraq, 92 Pakistan 89 and China. 85 One study involved five European countries (Denmark, Germany, Netherlands, Poland and Great Britain) to validate a pan-European questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“… 45 46 49 52 59 83 113 Of the remaining studies, four each were from Japan, 57 61 62 79 the Netherlands 55 102–104 and Thailand 67 69 95 105 ; three each from Germany, 58 75 108 Estonia, 71 78 115 Iran 48 76 84 and Vietnam 93 96 97 and two each were from Lebanon, 112 114 UAE, 60 86 Brazil 107 110 and Spain. 63 73 One each from Canada, 74 Finland, 99 New Zealand, 43 Lithuania, 44 Malaysia, 87 Poland, 91 Slovenia, 80 Serbia, 70 Sudan, 94 Nigeria, 109 Iraq, 92 Pakistan 89 and China. 85 One study involved five European countries (Denmark, Germany, Netherlands, Poland and Great Britain) to validate a pan-European questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Hospital pharmacists are key to complete the patient’s therapeutic management by connecting the patient (or caregivers) with physicians and other members of a patient’s health care team, ensuring that the highly complex hospital-based treatments are delivered, informed, understood and properly used by the patient, both in the inpatient and outpatient setting. On the other hand, community pharmacists, in addition to their role as dispensers of retail and prescription outpatient medication, are also highly accessible points of therapeutic information and healthcare assistance that may substantially impact on patient care ( 17 ) and satisfaction ( 18–21 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study identified that accessibility, respect, communication skills and a friendly behavior from pharmacists are considered as trust enhancing factors [ 36 ]. The average time of consultation was from 1 to 5 min, however, the lack of time due to the economic situation and the decrease in the number of employees in the pharmacies are examples of obstacles in front of good counseling to patients and was reported in one previous study [ 6 ]; this was also similar to a study conducted in Portuguese community pharmacies with a mean duration of 3.98 min per interaction between the patient and community pharmacist [ 37 ].The inadequate perception of customers meets also the results of a regional study in Baghdad that recommended allocation of more time for patient counseling, helping patients to manage their medications and extend their working hours to meet customer needs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%